Pilea umbrosa ameliorate CCl4 induced hepatic injuries by regulating endoplasmic reticulum stress, pro-inflammatory and fibrosis genes in rat - Irum Naz; Muhammad Rashid Khan; Jawaid Ahmed Zai; Riffat Batool; Zartash Zahra; Aemin Tahir (Komiyama Printing Co. Ltd, 2020)
Abstract Background Pilea umbrosa (Urticaceae) is used by local communities (district Abbotabad) for liver disorders, as anticancer, in rheumatism and in skin disorders. Methods Methanol extract of P. umbrosa (PUM) was investigated for the presence of polyphenolic constituents by HPLC-DAD analysis. PUM (150 mg/kg and 300 mg/kg) was administered on alternate days for eight weeks in rats exposed with carbon tetrachloride (CCl4). Serum analysis was performed for liver function tests while in liver tissues level of antioxidant enzymes and biochemical markers were also studied. In addition, semi quantitative estimation of antioxidant genes, endoplasmic reticulum (ER) induced stress markers, pro-inflammatory cytokines and fibrosis related genes were carried out on liver tissues by RT-PCR analysis. Liver tissues were also studied for histopathological injuries. Results Level of antioxidant enzymes such as catalase (CAT), superoxide dismutase (SOD), peroxidase (POD) and glutathione (GSH) decreased (p < 0.05) whereas level of thiobarbituric acid reactive substance (TBARS), H2O2 and nitrite increased in liver tissues of CCl4 treated rat. Likewise increase in the level of serum markers; alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP) and total bilirubin was observed. Moreover, CCl4 caused many fold increase in expression of ER stress markers; glucose regulated protein (GRP-78), x-box binding protein1-total (XBP-1 t), x-box binding protein1-unspliced (XBP-1 u) and x-box binding protein1-spliced (XBP-1 s). The level of inflammatory mediators such as tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) and monocyte chemoattractant protein-1 (MCP-1) was aggregated whereas suppressed the level of antioxidant enzymes; γ-glutamylcysteine ligase (GCLC), protein disulfide isomerase (PDI) and nuclear erythroid 2 p45-related factor 2 (Nrf-2). Additionally, level of fibrosis markers; transforming growth factor-β (TGF-β), Smad-3 and collagen type 1 (Col1-α) increased with CCl4 induced liver toxicity. Histopathological scrutiny depicted damaged liver cells, neutrophils infiltration and dilated sinusoids in CCl4 intoxicated rats. PUM was enriched with rutin, catechin, caffeic acid and apigenin as evidenced by HPLC analysis. Simultaneous administration of PUM and CCl4 in rats retrieved the normal expression of these markers and prevented hepatic injuries. Conclusion Collectively these results suggest that PUM constituted of strong antioxidant chemicals and could be a potential therapeutic agent for stress related liver disorders.